Quality control of pasteurized milk products in aluminum foil packaging at dairy a, sleman, special region of yogyakarta - Permana, Bayu Dwi; Juwitaningtyas, Titisari (Journal of Halal Science and Research, 2022)
Milk is a dairy farm product that contains various kinds of nutrients needed by humans. Bacteria easily contaminate milk, so it has a concise shelf life. One way to prevent bacterial contamination is by pasteurization. According to SNI 01-3951-1995, pasteurized milk has gone through a heating process of 72℃ for 15 seconds or heating at a temperature of 63-66℃ for 30 minutes. Company A's aluminum foil packaging pasteurized milk products are often defective. The defect is caused during the processing, preservation, and storage of milk that is not good. Therefore, quality control must be carried out in the pasteurization process of milk to ensure the quality of milk is maintained. Quality control is a process to assist in achieving products following the objectives. Quality control in the pasteurization process in company A needs to be discussed further to prevent defects in pasteurized milk in aluminum foil packaging. Attributes that affect milk quality are pH, color, texture, and aroma. The method used to determine the defect to milk is adjusted to the production in company A by taking 30% samples with a total of 3 production batches which are then analyzed for the type of defect, pH analysis with control charts, organoleptic quality analysis with scoring diagrams, and fishbone diagrams to determine the causative factors defect.